Scope and future prospects of oil palm plantation in Arunachal Pradesh - Singh, Raghuveer; Kangjam, Valenta; Angami, T.; Wangchu, L. (Indian Horticulture, 2025)
Arunachal Pradesh holds immense potential for oil palm cultivation under the National Mission on Edible Oils–Oil Palm (NMEO-OP), with 133,811 hectares identified, yet only 5,677 hectares is currently planted. High-yielding Tenera hybrids (up to 25 MT/ha) offer farmers a lucrative, low-maintenance crop with significant carbon sequestration benefits. Government support for planting material imports, quarantine, and processing industries is accelerating growth. While the region is currently free from major insect pests, proactive monitoring remains essential. With strong policy backing and infrastructure development, oil palm can significantly boost India’s edible oil self-sufficiency while transforming Arunachal’s agricultural economy.